Predicting Fully-developed Channel Flow with Zero-equation Model - Rahman, MM; Hasan, K; Liu, Wenchang; Li, Xinming (MIST International Journal of Science and Technology, 2022)
A new zero-equation model (ZEM) is devised with an eddy-viscosity formulation using a stress length variable which the structural ensemble dynamics (SED) theory predicts. The ZEM is distinguished by obvious physical parameters, quantifying the underlying flow domain with a universal multi-layer structure. The SED theory is also utilized to formulate an anisotropic Bradshaw stress-intensity factor, parameterized with an eddy-to-laminar viscosity ratio. Bradshaw’s structure-function is employed to evaluate the kinetic energy of turbulence k and turbulent dissipation rate ee. The proposed ZEM is intrinsically plausible, having a significant impact on the prediction of wall-bounded turbulence. MIJST, Vol. 9(2), December 2021: 17-22